Hubungan Beban Kerja Dengan Gangguan Nyeri Bahu Pada Fisioterapis Di Rumah Sakit Wilayah Jawa Timur - Ainun, Nurul; Hargiani, Fransisca Xaveria; Kusuma, Wahyu Teja; Halimah, Nurul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective : To identify the association of workload with shoulder pain complaints in worker in East Java Region hospital. Methods : This article were descriptive correlational type with data collection techniques carried out by questionnaires. Collecting respondent data by sending a questionnaire with the technique of sending a google form with a link is https://forms.gle/urgLDUPQtPCeycQv5 to all physiotherapists in East Java region, then from the results of respondents who sent data there were 152 physiotherapists. Then the data is reduced which is in accordance with the criteria, namely respondents who work in hospitals and who have experienced shoulder pain. From these data, the researcher can present it and conclude. Results : The result showed that the physiotherapist's age range is 22-56 years. The results of research on physiotherapists who work in hospitals type A, B and C in East Java region who have sent data are 68.4% of physiotherapists who experience shoulder pain complaints, for those who experience a minimum of complaints are 35,6%, mild is 45,2%, moderate 13,5% and 5,8% for severe complaints. Conclusion : The workload of physiotherapists has a significant relationship with complaints of perceived shoulder pain. In other words, the heavier the workload will increase the severity of shoulder pain complaints felt by the physiotherapist.